Particle Engineering by Dense Gas Technologies Applied to Pharmaceuticals - Foster, Neil; Mammucari, R.; Danh, L.; Teoh, W. (2012)
Dense phase carbon dioxide is used in pharmaceutical processingsince it is nontoxic, nonflammable, inexpensive, and easily accessible. For decades it has been utilized in food and chemical processing due to its ability to provide a high degree of purification, and to produce submicron particles with uniform particle size distribution. In recent years, DPCD technology has been explored and used in pharmaceutical processing to obtain ultra-high-purity active pharmaceutical ingredients and, more significantly, to modify their physical characteristics regarding particle size distribution, crystalline structure, and surface topography crucial for the drugs stability, bioavailability, ease of delivery, and clinical performance. The aim of this chapter is to describe the application of dense phase CO 2 as a solvent or antisolvent to pharmaceutical processes, presenting the experimental equipment, the main results obtained from the application of the technology, and the advantages of using pressurized CO 2 . © 2012 Blackwell Publishing Professional.